2010
DOI: 10.1152/jn.00396.2010
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channels Set Spike Timing Regularity of Mammalian Vestibular Afferent Neurons

Abstract: Kalluri R, Xue J, Eatock RA. Ion channels set spike timing regularity of mammalian vestibular afferent neurons. J Neurophysiol 104: 2034-2051, 2010. First published July 21, 2010 doi:10.1152/jn.00396.2010. In the mammalian vestibular nerve, some afferents have highly irregular interspike intervals and others have highly regular intervals. To investigate whether spike timing is determined by the afferents' ion channels, we studied spiking activity in their cell bodies, isolated from the vestibular ganglia of y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
166
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(208 citation statements)
references
References 78 publications
27
166
0
Order By: Relevance
“…We therefore tested the effects of removing I h on the zero current potential, action potential, and EPSPs in calyces. In ruptured and perforated patch clamp recordings from vestibular primary neurons, spontaneous action potentials are not usually observed, however, action potentials have been evoked in whole-cell current clamp in calyces (Rennie and Streeter 2006;Dhawan et al 2010) and vestibular ganglion somata (Limón et al 2005;Risner and Holt 2006;Iwasaki et al 2008;Kalluri et al 2010). We evoked action potentials by delivering repeated hyperpolarizing current injections in current clamp and also observed spontaneous EPSPs between action potentials (Fig.…”
Section: Effects Of I H In Current Clampmentioning
confidence: 68%
See 4 more Smart Citations
“…We therefore tested the effects of removing I h on the zero current potential, action potential, and EPSPs in calyces. In ruptured and perforated patch clamp recordings from vestibular primary neurons, spontaneous action potentials are not usually observed, however, action potentials have been evoked in whole-cell current clamp in calyces (Rennie and Streeter 2006;Dhawan et al 2010) and vestibular ganglion somata (Limón et al 2005;Risner and Holt 2006;Iwasaki et al 2008;Kalluri et al 2010). We evoked action potentials by delivering repeated hyperpolarizing current injections in current clamp and also observed spontaneous EPSPs between action potentials (Fig.…”
Section: Effects Of I H In Current Clampmentioning
confidence: 68%
“…V 1/2 for I h in early postnatal (P5-P8) mouse primary vestibular ganglion cells averaged −110 mV (Chabbert et al 2001b), and we found a mean V 1/2 of −123 mV in control gerbil calyces. Therefore, I h is substantially activated at potentials more hyperpolarized than the mean resting potential, which averaged −61 mV in our isolated calyx terminals and −68 mV in vestibular ganglion neurons (Kalluri et al 2010). A Currents were simulated in response to a voltage protocol from a holding potential of -79 mV, followed by a 40-ms prepulse to −129 mV and subsequent test steps from −89 to +19 mV in 10-mV increments.…”
Section: H Properties-magnitude and Voltage Range Of Activationmentioning
confidence: 99%
See 3 more Smart Citations